Calibration and Validation of CN Values for Watershed Hydrological Response - Nanang S. Rizal; Iskandar Umarie; Kukuh Munandar; Ari Eko Wardoyo (Salehan Institute of Higher Education, 2023)
The amount of rainfall can be used to estimate the runoff that enters a reservoir. Runoff is influenced by land use, and soil type greatly affects the amount of runoff that will occur. This study discusses the development of a hydrological model with the application of the Hydrologic Engineering Center (HEC-HMS) in the Karangmumus watershed using soil data that has been verified in the field and divided into soil zones based on soil permeability testing in the laboratory. With the help of Geographic Information System (GIS) and Geospatial Hydrological Model (HEC-GeoHMS) applications, it is possible to identify the flow of the Karangmumus watershed and the Lempake Dam in Kalimantan by simulating the rain runoff process. The hydrological model was developed in the HEC-HMS by recording daily rainfall events from 2009 to 2019. With a daily period, then, the zoning soil type data was entered based on the results of soil permeability testing with the help of the application of the soil conservation curve method (SCS-CN), then discharge transformation, and calculation of water loss, including routing with Muskingum and SCS-Hydrograph applications. Based on the distribution of the CN value, the theoretical runoff is calculated and then calibrated with the observed discharge in 2017 and 2018, and then validated with the observed discharge in 2019, showing good results with a coefficient of determination between 0.89 to 0.92. Doi: 10.28991/CEJ-2023-09-01-06 Full Text: PDF